Physical modelling in reduced dimensions of contention walls made of reinforced earth by Geo-textile (2007)
A machine wasbuilt with the purpose to try physical modelling by making reinforced earth retaining walls with geo-textile. The machine reinforced earth retaining walls with geo-textile. The machine consists in a prismatic steel frame with steel sheet walls, including one in acrylic. The models was used sand out of washed rock, and as reinforcement was used an especial fabric, which underwent the standard testing in the factory PAVCO.  The model 0.80 m long and 0.20 m wide, full of sand reinforced with the fabric. A total of 6 models were made whith different thickness of reinforced layer. The models were subject to a comprension load, and during the loading process it was observed the failure mechanism and stress-displacement behavior.